The aquatic particle number quandary - Bochdansky, Alexander B.; Huang, Huanqing; Conte, Maureen H. (Frontiers in Marine Science, 2022)
Optical surveys of aquatic particles and their particle size spectra have become important tools in studies of light propagation in water, classification of water masses, and the dynamics of trophic interactions affecting particle aggregation and flux. Here, we demonstrate that typical settings used in image analysis vastly underestimate particle numbers due to the particle – gel continuum. Applying a wide range of threshold values to change the sensitivity of our detection system, we show that macrogels cannot be separated from more dense particles, and that a true particle number per volume cannot be ascertained; only relative numbers in relation to a defined threshold value can be reported. A quandary thus presents itself between choosing a detection threshold low enough to accurately record orders of magnitude more particles on one hand or selecting a higher threshold to yield better image quality of plankton on the other. By observing the dynamics of coagulation and dissolution steps unique to cation-bridged gels abundant in aquatic systems, we find naturally occurring gels, and microscopic particles attached to them, to cause the ill-defined particle numbers. In contrast, the slopes in particle number spectra remained largely unaffected by varying sensitivity settings of the image analysis. The inclusion of fainter particles that are not typically captured by imaging systems provides a window into the true microscale spatial heterogeneity at scales relevant to small plankton organisms and processes that are dependent on particle density such as surface-associated chemical reactions as well as particle coagulation and aggregation dynamics.